Increased Activity and Learning Outcomes Using the WhatsApp and Google Form Applications in the Covid-19 Pandemic Period - Rahmadi, Rahmadi (Science Education and Application Journal, 2021)
This study aims to describe the increase in student activity and learning outcomes through distance learning using the WhatsApp and Google form applications during the Covid-19 pandemic. The subjects of this study were 36 students of class X TKRO 3 SMKN 1 Bulakamba Academic Year 2020/2021. This research is a quantitative study using descriptive methods. This study aims to describe the increase in student activity and learning outcomes through distance learning using the WhatsApp and Google form applications during the Covid-19 pandemic. The subjects of this study were 36 students of class X TKRO 3 SMKN 1 Bulakamba Academic Year 2020/2021. This research is a quantitative study using descriptive methods with operational stages: (1) preparing a Learning Implementation Plan (RPP). (2) preparing learning materials, assignments and daily tests. (3) upload learning materials on the class WhatsApp group. (4) students study learning materials using cellphones / laptops. (5) monitoring the implementation of the learning process. (6) students work on and upload assignments. (7) provide daily feedback and tests using Google form. The implementation of distance learning with the WhatsApp and Google form applications can increase student learning activities from 88.89% to 93.52% or an increase of 5.20% and can increase the average value of learning outcomes from 77.53 to 80.13 or increased by 3.34%.